DEVELOPMENT OF INDONESIAN LANGUAGE TEXTBOOKS BASED ON LOCAL WISDOM TO IMPROVE STUDENTS' READING SKILLS - Rizki Aria; Venni Arviani (Jurnal Penelitian Progresif, 2025)
The development of Indonesian language textbooks is very important, especially textbooks that integrate local wisdom. Existing textbooks have not fully used local wisdom in their learning, especially in Indonesian language learning. This research aims to produce a product in the form of textbooks. The research method used is Thiagarajan's 4D research and development. The results showed that the textbook developed was suitable for use. The feasibility of the book products developed based on material assessment obtained 91.87 with very good criteria, media expert assessment obtained 91.35 with very good criteria, design expert assessment obtained 90 with very good criteria. Based on the acquisition of these validation results, it can be said that the textbook products developed are feasible and can be used in the field.